1984
DOI: 10.1002/pssa.2210820212
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of image contrast from extrinsic stacking faults

Abstract: A quantitative study is made of the contrast from extrinsic stacking faults in silicon imaged under “weak‐beam” conditions in the electron microscope. The contrast is studied as a function of the inclination of the fault to the electron beam direction. It is shown that, within the experimental error, the contrast agrees with an analysis based upon standard scattering theory and a fault of finite width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The situation for an intrinsic fault is not so clear. The kinematical theory predicts no asymmetry for an intrinsic fault with reversal of the sign of (g.R)s, contrary to what was observed [22,24,25]. Even for an intrinsic fault, electronic bond redistribution at the fault is to be expected, so that the fault region might appear to have a thickness.…”
Section: Weak-beam Contrast Asymmetry For Stacking Faultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The situation for an intrinsic fault is not so clear. The kinematical theory predicts no asymmetry for an intrinsic fault with reversal of the sign of (g.R)s, contrary to what was observed [22,24,25]. Even for an intrinsic fault, electronic bond redistribution at the fault is to be expected, so that the fault region might appear to have a thickness.…”
Section: Weak-beam Contrast Asymmetry For Stacking Faultsmentioning
confidence: 61%
“…For s sufficiently large, the periodicity is comparable with the thickness of the fault, and this needs to be taken into account in the kinematical theory. A treatment so based was given by Föll, Carter and Wilkens [24], which suggested that an extrinsic fault would exhibit contrast asymmetry with change of sign of (g.R)s. This was confirmed by a quantitative study of Cockayne et al [25]. The situation for an intrinsic fault is not so clear.…”
Section: Weak-beam Contrast Asymmetry For Stacking Faultsmentioning
confidence: 85%
“…This effect, which can amount almost to disappearance of the defect in one of the two images, was first observed for extrinsic stacking faults by Cullis & Booker (1972) but has also been reported for some intrinsic stacking faults (FO11 et al, 1980;Cockayne et al, 1984) as well as for (1 13) planar defects in Ge (Ferreira Lima & Howie, 1976) and for grain boundaries (Carter & FOll, 1978). The effect is particularly pronounced for defects on planes whose normal makes a large angle B with the incident beam direction.…”
Section: Asymmetries In W E a K Beam Images Of P L A N A R Defectsmentioning
confidence: 78%
“…Thus, for example, image-contrast anomalies which are not totally explained can be found in stack-ing fault images under WB diffraction conditions (Foll et al, 1980;Botros et al, 1981;Cockayne et al, 1984). Another difficulty arises with twin boundaries which are commonly obtained in small metallic particles grown with this technique.…”
Section: Introductionmentioning
confidence: 93%